Did a workplace sugar-sweetened beverage sales ban reduce anxiety-related sugar-sweetened beverage consumption during the COVID-19 pandemic? - Laurie M Jacobs; Laura A Schmidt; Dean Schillinger; Jamey M Schmidt; Katie E Alegria; Bethany Parrett; Amanda Pickett; Elissa S Epel (Cambridge University Press, 2024)
Abstract Objective: Workplace sugar-sweetened beverage (SSB) sales bans can reduce SSB consumption. Because stress and anxiety can promote sugar consumption, we examined whether anxiety among hospital employees during the COVID-19 pandemic was associated with changes in SSB consumption and explored whether this relationship varied by exposure to a workplace SSB sales ban. Design: In a prospective, controlled trial of workplace SSB sales bans, we examined self-reported anxiety (generalised anxiety disorder-7) and self-reported SSB consumption (fluid ounces/d) before (July 2019) and during (May 2020) the COVID-19 pandemic. Setting: Hospital sites in two conditions (four with SSB sales bans and three without sales bans) in Northern California. Participants: We sampled 580 participants (hospital employees) from a larger trial of sales bans; all were regular consumers of SSB (minimum 3/week at main trial enrollment). This subsample was chosen based on having appropriately timed data for our study questions. Results: Across conditions, participants reduced SSB consumption over the study period. However, participants with higher pandemic-era anxiety scores experienced smaller reductions in SSB consumption after 9 months compared with those with lower anxiety scores (β = 0·65, P < 0·05). When the sample was disaggregated by sales ban condition, this relationship held for participants in the control group (access to SSB at work, β = 0·82, P < 0·05), but not for those exposed to an SSB sales ban (β = 0·42, P = 0·25). Conclusions: SSB sales bans likely reduce SSB consumption through multiple pathways; buffering stress-related consumption may be one mechanism.